Inter-domain routing method under normalized Quality of Service based on hierarchical coordination - Lemeshko, O.; Yevdokymenko, M.; Hu, Z.; Yeremenko, O. (ХНУРЕ, 2020)
The inter-domain routing method under normalized Quality of Service (QoS) based on hierarchical coordination in a Software-Defined Network (SD-WAN, Hybrid SD-WAN) is proposed in the paper. The novelty of the method is that the routing solutions are aimed at ensuring the normalized QoS in terms of average transmission rate and average end-to-end packet delay. The method is based on the use of a decomposition flow-based routing model, which consists of the inter-domain routing interaction and ensuring the normalized QoS conditions that obtained during tensor network modeling. Therefore, the inter-domain QoS routing problem was presented as an optimization problem with a quadratic optimality criterion. A number of numerical examples confirmed the efficiency and effectiveness of the proposed method in terms of providing the normalized QoS within the finite number of iterations. Reducing the number of such iterations helps to decrease the amount of service traffic transferred between routers and SDN controllers at different levels, as well as minimize the time for solving the inter-domain QoS-routing task.
Keywords: Method; Inter-domain routing; Hierarchical coordination; Quality of Service; End-to-end delay; SDN